2019
DOI: 10.1371/journal.pone.0222607
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Epstein-Barr virus, human papillomavirus, cytomegalovirus and herpes simplex virus type 1 in patients with diabetes mellitus type 2 in south-eastern Poland

Abstract: A microbiota is a complex ecosystem of microorganisms consisting of bacteria, viruses, protozoa, and fungi living in different niches of the human body, which plays an essential role in many metabolic functions. Modifications in the microbiota composition can lead to several diseases, including metabolic disorders. The aim of this study was to analyze the prevalence of four viruses which can cause persistent infections–Epstein-Barr virus (EBV), human papillomavirus (HPV), cytomegalovirus (CMV), and herpes simp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…Our previous research revealed that the prevalence of EBV DNA in patients with diabetes is significantly higher than in individuals without this disease [16]. The present study analyzed the serum activity of GPx and SOD in the patients with DM2 with and without EBV infection.…”
Section: A1111111111 A1111111111 A1111111111 A1111111111 A1111111111mentioning
confidence: 85%
See 1 more Smart Citation
“…Our previous research revealed that the prevalence of EBV DNA in patients with diabetes is significantly higher than in individuals without this disease [16]. The present study analyzed the serum activity of GPx and SOD in the patients with DM2 with and without EBV infection.…”
Section: A1111111111 A1111111111 A1111111111 A1111111111 A1111111111mentioning
confidence: 85%
“…According to our researches both EBV infection and diabetes are associated with lower values of antioxidant enzymes. Our previous studies revealed that EBV DNA was detected more frequently in the group of diabetic patients (35.9%) than in patients without diabetes [16]. Chronic infections caused by various viruses influence the whole immunity of the patient.…”
Section: Plos Onementioning
confidence: 95%
“…As for the association between EBV DNA and clinical factors, there was no significant difference between EBV DNA and sex, age, remaining teeth, denture use, or medical history. Diabetic patients were more susceptible to oral EBV than non-diabetic patients (15). Thus, diabetes is thought to be an important risk factor in the prevalence of oral EBV DNA.…”
Section: Discussionmentioning
confidence: 94%
“…However, it remains unknown whether EBV is associated with poor oral health (i.e., dental plaque accumulation, an increased oral bacterial count, and a small number of remaining teeth) among middle-aged and older Japanese people. Smoking and diabetes are strongly related to oral EBV prevalence (14,15). However, the relationship between periodontitis and EBV has not been fully elucidated by reducing the effects of confounding factors (i.e., smoking and a medical history of diseases such as diabetes).…”
Section: Introductionmentioning
confidence: 99%
“…In humans carrying the CCR5delta32 allele, the age of diabetes type 1 onset was delayed and morbidity due to diabetes type 2 was reduced [73]. In Australian and New Zealand populations, partial protection from diabetes type 1 was observed in individuals homozygous for the CCR5delta32 allele [74]. At the same time, CCR5 down-regulation in cell cultures promoted a protective mechanism against cellular destruction in diabetes type 1 [75].…”
Section: Ccr5 Ad and Diabetesmentioning
confidence: 99%